Reflections on the use of arbitrary procedures and the specialized mathematical content knowledge of elementary school teachers - Dávila Vargas, Kelly Jennifer (2024)
This essay suggests that when an elementary school teacher has an instrumental understanding of the mathematical content, they rely on arbitrary procedures or “shortcuts” to teach. In other words, they resort to mechanical steps to solve problems or operations, often oversimplifying the underlying concepts. Based on the Mathematical Knowledge for Teaching framework proposed by Ball et al. (2008) and the Knowledge of Topics (KoT) proposed by Carrillo-Yañez et  al. (2018), this essay delves into the domains of knowledge involved in teaching mathematics, emphasizing the specialized content knowledge domain. This domain goes beyond merely solving problems or executing operations accurately; it implies a profound comprehension of the underlying mathematical concepts and their interconnectedness. Through the analysis of some “shortcuts” used by elementary school teachers, the authors seek to promote reflections on the importance of specialized content knowledge in teacher education.